Age-Related Sensory Impairment and Cognitive Decline in Geriatric - Pratiwi, Dewi; Anggraini, Aulia Hervi; Bayu, Febri Arianto (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2020)
Background: Incidence of sensory impairment and cognitive decline were increase with aging, each would give a considerable impact on public health and quality of life especially in geriatric population. Several mechanisms have been proposed to account for the correlation between sensory impairment and cognitive decline and the common mechanisms were sensory deprivation, information degradation, cognitive load, resource allocation and or social isolation. Prolonged reductions in the quality or quantity of sensory input lead to cognitive deterioration due to neuronal atrophy. This study aimed to determine whether age related sensory impairment with cognitive decline.Subjects and Method: This was a cross-sectional study design conducted at geriatric clinic, Dr. Moewardi General Hospital, Surakarta, from May 31 to July 1, 2018. A sample of 54 elderly aged ≥60 years old was selected by consecutive sampling. The dependent variable was cognitive decline. The independent variables were presbyacusis, presbyastasis, olfactory impairment, diabetes, and hypertension. Presbycusis was measured by Pure Tone Audiometry. Presbyastasis was measured by Dynamic Visual Acuity (DVA) test. Olfactory dysfunction was measured by sniffing test. Cognitive decline was assessed by MoCA-Ina questionnaire. The data were analyzed by Chi-square test.Results: The mean age of subjects was 70.5 years old ranging from 61-81 years old and most of the subjects were females (72.2%). Pure tone audiometry test revealed that 44.4% patients had presbycusis. Dynamic Visual Acuity test showed that 25.9% patients had presbyastasis. Sniffing test revealed that 29.6% patients had olfactory dysfunction. Presbyacusis (OR= 11.9; 95% CI= 1.3 to 105.5; p= 0.008) and olfactory dysfunction (OR= 10.8; 95% CI= 1.8 to 61.9; p= 0.002) increased cognitive decline, and they were statistically significant. Presbyastasis decreased cognitive decline (or= 0.9; 95% CI= 0.1 to 5.3; p= 0.948), but it was statistically non-significantConclusion: Sensorineural health may serve as a marker of brain aging therefore sensory measures can be used as screening tools for cognitive decline risk.Keywords: sensory impairment, presbycusis, presbyastasis, olfactory dysfunction, cognitive declineCorrespondence: Dewi Pratiwi. Department of Otorhinolaryngology Head and Neck Surgery, Dr. Moewardi Hospital/ Faculty of Medicine, Universitas Sebelas Maret Surakarta, Central Java. Email: pratiwidewi81@gmail.comIndonesian Journal of Medicine (2020), 05(02): 153-161https://doi.org/10.26911/theijmed.2020.05.02.10